Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(3x^3-7x^2+17x-5\)
\(=3x^3-6x^2-x^2+15x+2x-5\)
\(=\left(-6x^2+2x\right)+\left(3x^3+15x\right)-\left(x^2+5\right)\)
\(=-2x\left(3x-1\right)+3x\left(x^2+5\right)-\left(x^2+5\right)\)
\(=-2x\left(3x-1\right)+\left(x^2+5\right)\left(3x-1\right)\)
\(=\left(3x-1\right)\left(-2x+x^2+5\right)\)
\(6x^2+xy-7x-2y^2+7y-5=-\left(y-2x-1\right)\left(2y+3x-5\right)\)
Trả lời:
\(6x^2+xy-7x-2y^2+7y-5=-\left(y-2x-1\right)\left(2y+3x-5\right)\)
Hok_tốt nha
\(3x^3-7x^2+17x-5.\)
\(=3x^3-x^2-6x^2+2x-15x+5\)
\(=\left(3x^3-x^2\right)-\left(6x^2-2x\right)-\left(15x-5\right)\)
\(=x^2\left(3x-1\right)-2x\left(3x-1\right)-5\left(3x-1\right)\)
\(=\left(3x-1\right)\left(x^2-2x-5\right)\)
7x - 6x^2 - 2
= - ( 6x^2 - 7x + 2 )
= - ( 6x^2 - 3x - 4x + 2)
= - [ 3x( 2x - 1) - 2(2x - 1)]
= - ( 2x - 1)( 3x - 2)
2 /
2x^2 + 3x - 5
= 2x^2 + 5x - 2x - 5
= x ( 2x+5) - ( 2x+ 5)
=( x - 1)( 1x+ 5)
3/ 16x - 5x^2 - 3
= - ( 5x^2 - 16x + 3)
= - (5x^2 - x - 15x + 3)
= - [ x( 5x - 1) - 3 ( 5x - 1)]
= - [ (x - 3)( 5x - 1)]
= - ( x- 3)( 5x - 1)
\(6x^2-7x+2=6x^2-3x-4x+2=3x\left(2x-1\right)-2\left(2x-1\right)=\left(3x-2\right)\left(2x-1\right)\)
Đúng cho mình nhe
Dễ mà ^_^: 3x2-7x+2=3x2 -x-6x+2=(3x2-x)-(6x-2)=x(3x-1)-2(3x-1)=(3x-1)(x-2)
sửa đề xíu:
\(2x^2+7x+5=2x^2+2x+5x+5=\left(2x^2+2x\right)+\left(5x+5\right)=2x\left(x+1\right)+5\left(x+1\right)=\left(x+1\right)\left(2x+5\right)\)
`2^2` à bạn?